DESARROLLO DE PROTOTIPO AUTOMATIZADO PARA EL MONITOREO DE VARIABLES DE LA COMPOSTERA DE LA TECNOACADEMIA NEIVA. - Aldana Pulido , Deiber Andrés
The objective of the research is to develop an automated prototype for monitoring variables of the Neiva Tecnoacademia Composter with IoT, donated by the Italo Latin American IILA Institute, which has the capacity to produce 0.1 tons per month of compost; Although it is a smart composter and works with clean energy from the sun, some of its tasks are manual, such as monitoring variables and sprinkling water to keep humidity controlled, tasks carried out by apprentices. responsible for its operation, this can cause human errors to be induced in the composting process, which can cause alterations in the aerobic process of organic matter, obtaining a lower quality fertilizer. The methodological approach is experimental development, for its execution the following phases were carried out: Investigation, Hardware and software development, and Prototyping and validation. As results, the implementation of a humidity and temperature monitoring system for two compartments of the compost bin was obtained using sensors and the ESP32 programmable card that incorporates IoT through a Wi-Fi connection in real time, the reading of the variables is shown through a screen 16x2 LCD locally and in the cloud through a graphical interface (dashboard) on the Arduino IoT Cloud platform; To control humidity, an irrigation system activated by solenoid valves was implemented through an ON – OFF control. With the implementation of the prototype, it was possible to automate the process of monitoring variables and controlling the humidity of the compost, significantly increasing the quality of the prepared compost and reducing the work of the apprentice composter operators.